Semiotika al-Qur’an: Pendekatan Baru Studi Islam (Telaah atas Asma’ al-Qur’an) - Solahudin Sanusi (JURNAL INDO-ISLAMIKA, 2011)
The Integration-Interconnection Paradigm requires the use of new approaches in Islamic studies, including the study of the Qur'an. Semiotics is one of the modern and post-modern approaches that are recently favored. This article intends to look at the principles of semiotics and how to exemplify their application in the study of the Qur'an. This approach is seen as able to provide developments for Asma 'al-Qur'an' theory which has so far seen stagnant. This approach has the potential to bring the theory to a more progressive direction, namely as the Qur'an's self-identity.